(untitled) (Journal of Educational Sciences, 2022)
The article actualizes the need for a theoretical substantiation of the theory of learning and personality development at the stage of early, middle and late adulthood. The implicit theory of intelligence, synergetic and eutagogical approaches are considered; knowledge management approaches for the knowledge society (phenomena of explicit and implicit knowledge, knowledge flows, diffusion of knowledge and culture); ideas of peeragogy as Education 4.0. The continuity of “classical pedagogy → andragogy → heutagogy → peeragogy” is studied. The results of a survey of 1st year students about their implicit presentation of the doctrine are given. The survey involved 86 students of the Kazakh National University named after al-Farabi. It was found that 66.7% of students chose the understanding “learning is the acquisition of facts, methods, etc., which can be stored and applied in practice”, 25% – “learning is the accumulation of knowledge” and 4.8% “learning is it is the interpretation and understanding of reality”, and 3.6% “teaching is the understanding of meaning and determination of meaning”. The attitude of students to the principles of eutagogy and pyragogy has been studied. Most students approve of the principles of self-education. Key words: heutagogy, andragogy, synergetics, implicit theories of intelligence, personality development, self-education, knowledge management.